HUBUNGAN HAMBATAN MEMBACA DENGAN HASIL BELAJAR IPAS SISWA KELAS V DI SDN KELURAHAN MANGGARAI (STUDI KORELASIONAL PADA MUATAN IPS) - Putri Dianti; Mohammad Syarif Sumantri; Engga Dallion (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to examine the relationship between reading difficulties and science and social studies (IPAS) learning outcomes, particularly in the social studies content, among fifth-grade students at public elementary schools in Manggarai Village. A quantitative approach with a correlational research design was employed. The study population consisted of fifth-grade students from public elementary schools in Manggarai Village, with a sample of 67 students. Data were collected using a reading assessment to measure reading difficulties and an achievement test to assess students' learning outcomes in the social studies content of IPAS. The findings revealed a correlation coefficient of −0.564, indicating a moderate negative relationship between reading difficulties and learning outcomes. The coefficient of determination (R²) was 31.8%, suggesting that reading difficulties accounted for 31.8% of the variance in students' learning outcomes, while the remaining 68.2% was influenced by other factors beyond the scope of this study. These findings indicate that higher levels of reading difficulties are associated with lower learning outcomes in the social studies content of IPAS. It is expected that the results of this study will assist teachers in identifying students' reading difficulties at an early stage and implementing appropriate instructional strategies to improve learning outcomes.